Intra-individual comparison of 18F-sodium fluoride PET–CT and 99mTc bone scintigraphy with SPECT in patients with prostate cancer or breast cancer at high risk for skeletal metastases (MITNEC-A1): a multicentre, phase 3 trial. Issue 12 (December 2022) - Bénard, François; Harsini, Sara; Wilson, Don; Zukotynski, Katherine; Abikhzer, Gad; Turcotte, Eric; Cossette, Mariève; Metser, Ur; Romsa, Jonathan; Martin, Montgomery; Mar, Colin; Saad, Fred; et al.
Summary: Background: Detection of skeletal metastases in patients with prostate cancer or breast cancer remains a major clinical challenge. We aimed to compare the diagnostic performance of 99m Tc-methylene diphosphonate ( 99m Tc-MDP) single-photon emission CT (SPECT) and 18 F-sodium fluoride ( 18 F-NaF) PET–CT for the detection of osseous metastases in patients with high-risk prostate or breast cancer. Methods: MITNEC-A1 was a prospective, multicentre, single-cohort, phase 3 trial conducted in ten hospitals across Canada. Patients aged 18 years or older with breast or prostate cancer with a WHO performance status of 0–2 and with high risk or clinical suspicion for bone metastasis, but without previously documented bone involvement, were eligible. 18 F-NaF PET–CT and 99m Tc-MDP SPECT were done within 14 days of each other for each participant. Two independent reviewers interpreted each modality without knowledge of other imaging findings. The primary endpoint was the overall accuracy of 99m Tc-MDP SPECT and 18 F-NaF PET–CT scans for the detection of bone metastases in the per-protocol population. A combination of histopathological, clinical, and imaging follow-up for up to 24 months was used as the reference standard to assess the imaging results. Safety was assessed in all enrolled participants. This study is registered with ClinicalTrials.gov, NCT01930812, and is complete. Findings: Between July 11, 2014, and March 3, 2017, 290 patients were screened, 288 of whom were enrolled (64 participants with breast cancer and 224 with prostate cancer). 261 participants underwent both 18 F-NaF PET–CT and 99m Tc-MDP SPECT and completed the required follow-up for statistical analysis. Median follow-up was 735 days (IQR 727–750). Based on the reference methods used, 109 (42%) of 261 patients had bone metastases. In the patient-based analysis, 18 F-NaF PET–CT was more accurate than 99m Tc-MDP SPECT (84·3% [95% CI 79·9–88·7] vs 77·4% [72·3–82·5], difference 6·9% [95% CI 1·3–12·5]; p=0·016). No adverse events were reported for the 288 patients recruited. Interpretation: 18 F-NaF has the potential to displace 99m Tc-MDP as the bone imaging radiopharmaceutical of choice in patients with high-risk prostate or breast cancer. Funding: Canadian Institutes of Health Research.